Analisis Pengaruh Perbedaan Rasio Pitch Terhadap Efisiensi Pada Turbin Archimedes - Fakhrul Rozi; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The Archimedes turbine being studied is a type of water turbine for small-scale power plants where the screw water turbine is suitable for rivers in the Indonesian region because the turbine operation only requires a low turbine head, low price, and easy to apply. With the potential for the flow of Koboko waterfall, which is located in Kampar Regency, Riau Province, it is possible to install this screw-type water turbine. In the process of designing the thread of the Archimedes turbine, it is influenced by external parameters (outside turbine radius, turbine length, turbine slope, water flow rate, head) and internal parameters (radius in a turbine, ratio pitch, and the number of blades). The external parameters are determined by the location of the turbine placement while the internal parameters can be determined independently to get the maximum performance from the turbine. In this study, the parameters to be analyzed are internal parameters, namely the ratio pitch. There are two variations in the design of ratio the pitch (Pr) are: 1.5 Ro and 1.2 Ro. Tests are carried out to calculate how much efficiency the Archimedes turbine produces for each ratio pitch and compare each result. The result of this research is that the efficiency of the Archimedes turbine with a ratio of pitch 1.2 Ro is higher than that of a ratio of pitch 1.5 Ro with an efficiency value of 36.3668 %. This efficiency value is obtained at a water flow rate of 0.00009 m3/ s and a turbine tilt angle of 40˚. Keywords : Turbine screw, ratio pitch, head, discharge, angle of placement.